Ureidopyrazine Derivatives: Synthesis and Biological Evaluation as Anti-Infectives and Abiotic Elicitors - Ghada Bouz; Martin Juhás; Pavlína Niklová; Ondřej Janďourek; Pavla Paterová; Jiří Janoušek; Lenka Tůmová; Zuzana Kovalíková; Petr Kastner; Martin Doležal; Jan Zitko (Molecules, 2017)
Tuberculosis (TB) caused by Mycobacterium tuberculosis (Mtb) has become a frequently deadly infection due to increasing antimicrobial resistance. This serious issue has driven efforts worldwide to discover new drugs effective against Mtb. One research area is the synthesis and evaluation of pyrazinamide derivatives as potential anti-TB drugs. In this paper we report the synthesis and biological evaluations of a series of ureidopyrazines. Compounds were synthesized by reacting alkyl/aryl isocyanates with aminopyrazine or with propyl 5-aminopyrazine-2-carboxylate. Reactions were performed in pressurized vials using a CEM Discover microwave reactor with a focused field. Purity and chemical structures of products were assessed, and the final compounds were tested in vitro for their antimycobacterial, antibacterial, and antifungal activities. Propyl 5-(3-phenylureido)pyrazine-2-carboxylate (compound 4, MICMtb = 1.56 μg/mL, 5.19 μM) and propyl 5-(3-(4-methoxyphenyl)ureido)pyrazine-2-carboxylate (compound 6, MICMtb = 6.25 μg/mL, 18.91 μM) had high antimycobacterial activity against Mtb H37Rv with no in vitro cytotoxicity on HepG2 cell line. Therefore 4 and 6 are suitable for further structural modifications that might improve their biological activity and physicochemical properties. Based on the structural similarity to 1-(2-chloropyridin-4-yl)-3-phenylurea, a known plant growth regulator, two selected compounds were evaluated for similar activity as abiotic elicitors.